Development of Digital Diagnostic Test Instruments for Differentiated Learning Process in Elementary Schools - Asnawi Asnawi; Tengku Muhammad Sahudra; Dini Ramadhani; Ary Kiswanto Kenedi; Ghenny Aosi; Muhammad Rizky Wardhana; Nadhira Azra Khalil (Postgraduate, University of Mataram, 2023)
Developing diagnostic tests for differentiated learning in Kurikulum Merdeka is becoming increasingly important to address today's learning challenges. Diagnostic tests can help teachers more effectively identify students' needs and abilities so that they can improve learning effectiveness and better achieve learning goals in Kurikulum Merdeka. The aim of this research is to develop a digital diagnostic test instrument for the differentiated learning process for elementary school students that is valid and suitable for use. This research is development research. The product developed is a digital diagnostic test instrument. The results of the development research produced a digital diagnostic test instrument for the differentiated learning process in elementary schools that is valid and suitable for use in measuring the learning styles of elementary school students.